2004
DOI: 10.1130/b25277.1
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and isotopic mapping of preexisting crustal structures that influenced the location and development of the San Jacinto fault zone, southern California

Abstract: We examine the role of preexisting crustal structure within the Peninsular Ranges batholith on determining the location of the San Jacinto fault zone by analysis of geophysical anomalies and initial strontium ratio data. A 1000-km-long boundary within the Peninsular Ranges batholith, separating relatively mafi c, dense, and magnetic rocks of the western Peninsular Ranges batholith from the more felsic, less dense, and weakly magnetic rocks of the eastern Peninsular Ranges batholith, strikes north-northwest tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…A younger age (1.0 to 1.5 Ma) has been inferred from geologic mapping and stratigraphic studies Matti and Morton, 1993;Dorsey, 2001) and morphometric analysis that suggested that the Pleistocene slip rate may be faster than 20 mm/year (Kendrick et al, 2002). Geophysical and isotopic mapping shows that the fault zone formed along preexisting faults and crustal weaknesses in the Peninsular Ranges batholith when structural complications in San Gorgonio Pass transferred slip away from the San Andreas fault (Langenheim et al, 2004).…”
Section: Study Areamentioning
confidence: 97%
“…A younger age (1.0 to 1.5 Ma) has been inferred from geologic mapping and stratigraphic studies Matti and Morton, 1993;Dorsey, 2001) and morphometric analysis that suggested that the Pleistocene slip rate may be faster than 20 mm/year (Kendrick et al, 2002). Geophysical and isotopic mapping shows that the fault zone formed along preexisting faults and crustal weaknesses in the Peninsular Ranges batholith when structural complications in San Gorgonio Pass transferred slip away from the San Andreas fault (Langenheim et al, 2004).…”
Section: Study Areamentioning
confidence: 97%
“…Based on seismic and other data (Magistrale and Zhou, 1996;Lutter et al, 1999Lutter et al, , 2004Fuis et al, 2001Fuis et al, , 2003Fuis et al, , 2004Langenheim et al, 2000Langenheim et al, , 2004Yeats and Huftile, 1995), basin depths at the profile location are estimated to be 8-9 km for the Los Angeles basin, and 5 km for the San Fernando and San Gabriel basins. The seismic refraction model along the LARSE-1 line (Fuis et al, 2001) shows increasing velocities between 15-27 km beneath the Los Angeles basin with velocities of 6.1-6.5 km/s in the middle crust, and ∼6.7 km/s in the lower crust.…”
Section: The Los Angeles San Fernando and San Gabriel Basinsmentioning
confidence: 99%
“…A fourth basement type, structurally isolated and exposed only in the southeastern part of the San Gabriel Mountains (Fig. 2), has been tentatively correlated with Peninsular Ranges rocks (Matti et al, 1985;May, 1989), a correlation at odds with its magnetic signature (Anderson et al, 2004;Langenheim et al, 2004). These regional basement types have distinct gravity and magnetic characters, as discussed later.…”
Section: P E N I N S U L a R R A N G E S T R A N S V E R S E R A N G mentioning
confidence: 99%